Multicentre open label randomised controlled trial of immediate enhanced ambulatory ECG monitoring versus standard monitoring in acute unexplained syncope patients: the ASPIRED study. Issue 2 (23rd February 2023) - Reed, Matthew J; Grubb, Neil; Lang, Chris; Goodacre, Steve; O'Brien, Rachel; Weir, Christopher J; Thokala, Praveen; Freeman, Nicola; Blackstock, Caroline; Dinsmore, Lynn; Boyd, Julia; Adamestam, Imad; et al.
Abstract : Introduction: Diagnosing underlying arrhythmia in emergency department (ED) syncope patients is difficult. There is a evidence that diagnostic yield for detecting underlying arrhythmia is highest when cardiac monitoring devices are applied early, ideally at the index visit. This strategy has the potential to change current syncope management from low diagnostic yield Holter to higher yield ambulatory monitoring, reduce episodes of syncope, reduce risk of recurrence and its potential serious consequences, reduce hospital admissions, reduce overall health costs and increase quality of life by allowing earlier diagnosis, treatment and exclusion of clinically important arrhythmias. Methods and analyses: This is a UK open prospective parallel group multicentre randomised controlled trial of an immediate 14-day ambulatory patch heart monitor vs standard care in 2234 patients presenting acutely with unexplained syncope. Our patient focused primary endpoint will be number of episodes of syncope at 1 year. Health economic evaluation will estimate the incremental cost per syncope episode avoided and quality-adjusted life year gained. Ethics and dissemination: Informed consent for participation will be sought. The ASPIRED trial received a favourable ethical opinion from South East Scotland Research Ethics Committee 01 (21/SS/0073). Results will be disseminated via scientific publication, lay summary and visual abstract. Trial registration number: ISRCTN 10278811.